2017
DOI: 10.1021/jacs.7b05464
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism and Scope of Phosphinidene Transfer from Dibenzo-7-phosphanorbornadiene Compounds

Abstract: Dibenzo-7-phosphanorbornadiene compounds, RPA (A = CH or anthracene), are investigated as phosphinidene sources upon thermally induced (70-90 °C) anthracene elimination. Analysis of substituent effects reveals that π-donating dialkylamide groups are paramount to successful phosphinidene transfer; poorer π-donors give reduced or no transfer. Substituent steric bulk is also implicated in successful transfer. Molecular beam mass spectrometry (MBMS) studies of each derivative reveal dialkylamide derivatives to be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
93
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 94 publications
(97 citation statements)
references
References 65 publications
4
93
0
Order By: Relevance
“…As has been noted, the chemistry of singlet phosphinidenes with a π‐donating substituent such as RO, R 2 N, R 2 P, with or without coordinated metal, were disclosed at a certain level. However, to the best of our knowledge the only example of an RSP‐type complex was reported by Terlouw, that is, (thiohydroxy)phosphinidene (HSP) .…”
Section: Figurementioning
confidence: 89%
See 4 more Smart Citations
“…As has been noted, the chemistry of singlet phosphinidenes with a π‐donating substituent such as RO, R 2 N, R 2 P, with or without coordinated metal, were disclosed at a certain level. However, to the best of our knowledge the only example of an RSP‐type complex was reported by Terlouw, that is, (thiohydroxy)phosphinidene (HSP) .…”
Section: Figurementioning
confidence: 89%
“…Bertrand reported thermodynamically stabilized phosphinophosphinidenes by the lone pair of the adjacent phosphorus moiety . Cummins’ group revealed that π‐donating dialkylamide groups were paramount to successful phosphinidene transfer, poorer π‐donors gave reduced or no transfer . Bulky substituents were employed in both Bertrand and Cummins’ work to increase the stability of transient phosphinidenes.…”
Section: Figurementioning
confidence: 99%
See 3 more Smart Citations